2022
DOI: 10.1002/pd.6172
|View full text |Cite
|
Sign up to set email alerts
|

Fetal phenotypes of Mendelian disorders: A descriptive study from India

Abstract: Objective: Exome sequencing (ES)-based diagnosis of Mendelian diseases in the fetus is limited by paucity of phenotypic information. This study reports the comprehensive phenotypes of some fetuses with Mendelian disorders. Methods: Next generation technology-based sequencing of all coding regions of the genome (Exome sequencing) or targeted gene sequencing using Sanger or next generation platforms was performed in a cohort of deeply phenotyped, cytogenetically normal fetuses with morphological defects. Prenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The study selection process is demonstrated in the PRISMA flow diagram (Figure 1). Thirty studies fulfilled the eligibility criteria and were suitable for meta‐analysis (1583 cases) 4,7,9,10,22–47 . This included data from the NHS England prenatal exome sequencing pathway 39 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection process is demonstrated in the PRISMA flow diagram (Figure 1). Thirty studies fulfilled the eligibility criteria and were suitable for meta‐analysis (1583 cases) 4,7,9,10,22–47 . This included data from the NHS England prenatal exome sequencing pathway 39 .…”
Section: Resultsmentioning
confidence: 99%
“…For studies that met the inclusion criteria but provided inadequate phenotypic information, corresponding authors were contacted to request further data ( n = 57) of which 15 (26.3%) responded. Eleven studies provided extended data sets 4,9,10,27,29,37,40,43,46–48 . Supplementary Table highlights the characteristics of the included studies and Figure 2 shows the overall quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Second, the spectrum of prenatal phenotypes, even of Mendelian disorders with well-described postnatal phenotypes, is not well described and can represent a phenotype expansion. [12][13][14][15] Emerging evidence, for example, suggests that SCN2A, an epilepsy gene, can present prenatally with central nervous system structural anomalies. [16][17][18] Third, prenatal phenotypes are largely limited to structural findings with no understanding of functional or cognitive differences.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in 'reverse phenotyping', whereby personalized diagnostic workflows permit the identification of previously unrecognized clinical signs of an unexpected underlying genetic diagnosis. Identification of an association of clinical postnatal structural and dysmorphological findings (by detailed clinical or postmortem examination), histology and additional radiological features (sometimes using postmortem magnetic resonance imaging (MRI)) with the prenatal ultrasound scan findings has been noted to improve the diagnosis of monogenic disorders [15][16][17] . This highlights the importance of a detailed and complete prenatal ultrasound examination performed in a tertiary center, with input from geneticists with expertise in prenatal management, to identify subtle fetal dysmorphology such as abnormalities of the fetal profile (e.g.…”
mentioning
confidence: 99%